TATA CARA PERHITUNGAN, PENYETORAN, PELAPORAN, PENCATATAN PAJAK PERTAMBAHAN NILAI (PPN) PADA CV. JMJ - Tirtana, Alfian Putra; Harjanti, Wulandari (Transpublika Publisher, 2022)
This study aims to analyze the procedures for calculating, depositing, reporting, and recording Value Added Tax (VAT) CV. JMJ in 2020. The researchers in this study analyzed what CV. JMJ has complied based on Law Number 42 of 2009 concerning Value Added Tax (VAT). In practice, the researcher chose to use a qualitative method. The definition of qualitative method is a method that has the aim of providing an overview and an explanation of the main subject or core of the research, then described and explained in detail and in depth. The results show that CV JMJ has been designated as a Taxable Entrepreneur (PKP) by the KPP in 2020. VAT tax obligations start from the calculation, deposit, reporting, and recording/journaling of Value Added Tax on all purchase and sales transactions that occurred in the month running during 2020. After doing the research, CV. JMJ is a tax-abiding company because it uses the right way to calculate whether it is the tax charged from the transaction partner or the tax imposed on consumers or buyers, then CV. JMJ has never exceeded the specified time limit in making payments and reporting the VAT Period SPT in 2020, as well as CV. JMJ has recorded and journalized all transactions properly and correctly.